Mortalidad por sífilis congénita en la región de Sudamérica: una revisión de tema (2019)
Objective: to perform a review of published studies that analyze the association between congenital syphilis and morbidity and mortality in in the Americas. Methods: a search was made in the databases: Scielo, Bvs, Embase, LILACS, MEDLINE / PubMed, PLOS, Clinical key and ScienceDirect in order to extract original research studies associated with congenital syphilis and morbidity and mortality in the Region of the south América. Results: The behavior of congenital syphilis at present in the region of the Americas is associated with multiple risk factors that increase the probability of infection and morbidity and mortality in pregnant women. The clinical interventions carried out have not been able to detect early cases of OS, which makes it impossible to apply timely treatment of the disease